PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH UNTUK MENINGKATKAN MOTIVASI GURU - Lina Sriatik; Taufiq Harris; M. Furqon Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to describe and analyze the implementation of the transformational leadership style by the principal in improving teachers’ work motivation at UPT SDN Kedungmakam, Jatirogo District. As the main pillar of education, teachers require strong motivation to face the challenges of the teaching and learning process at the elementary school level. The main issue examined in this study is how the dimensions of transformational leadership are implemented and how they influence teachers’ work motivation. This research employed a qualitative approach using a descriptive method. The findings reveal that through role modeling (idealized influence), inspirational motivation, support for creativity (intellectual stimulation), and individualized consideration, the principal has successfully created a conducive working environment. The implementation of these transformational leadership dimensions has contributed to increasing teachers’ enthusiasm, commitment, and responsibility in carrying out their professional duties. The study concludes that transformational leadership is a key factor that significantly enhances both the intrinsic and extrinsic motivation of teachers in performing their professional responsibilities. Therefore, the effective implementation of transformational leadership by school principals plays an important role in improving teacher performance and supporting the achievement of educational goals.